Populasi Aspergillus flavus dan Kualitas Fisik Kacang Tanah dan Jagung Pada Industri Jajanan Khas Madura - Farid, Ulfa Maulida; Romdhani, Ahmad Mundzir; Jannah, Nur Roudatul (BEST Journal (Biology Education, Sains and Technology), 2024)
This study aims to identify the population of Aspergillus flavus  and the physical quality of peanuts and corns in the Madurese Snack industries. This study is conducted since September to December 2022. Sampling of peanuts and corns is carried out to a number of Madurese snack industries at Bangkalan and Sumenep. Identification of Aspergillus flavus  utilizes the Total Plate Count (TPC) test procedure with PDA media (Potato Dextrose Agar) and 1 ml of chloramphenicol antibiotic. The physical quality of peanuts and corns is determined by the analysis of whole seeds, broken/damaged seeds and wrinkled seeds. The identification result of Aspergillus flavus  population in the peanuts sample is 6x102 to 8x102 colonies/gr, while the Aspergillus flavus  population in the corns sample is 9x102 to 11x102 colonies/gr. The percentage of physical quality from 1kg peanut seeds is 93,6% whole seeds, 5.7% wrinkled seeds, and 0,7% damaged seeds. The quality of corn based on the percentage of whole, wrinkled and damaged seeds shows that 95.2% of the total 1kg of corn seeds is the whole seeds, 3.7% is wrinkled and 1.1% are damaged seeds. The sample of peanuts and corns in several Madurese snack industries is above the maximum limit of microbe (mold and yeast) based on the Regulation of Indonesian Food and Drug Authority (BPOM) number 13 2019 about the stipulation of maximum limit for mold and yeast contamination in dry vegetable and grains that is 1.0 x 102 colonies/g.